Determinação do potencial de ocorrência de sistemas convectivos de mesoescala para a América do Sul - Rasera, Gustavo (2017)
This work presents a study aimed at improving the prediction of Mesoscale Convective Systems (MCSs) in the South America subtropical region through the development of a specific index for this type of meteorological system, as well as wind gusts forecasting applications and their potential in operational use in weather forecast. Using satellite imagery in the thermal infrared channel it was possible to obtain the 115 MCSs and 382 cases of unorganized convection that occurred between 2005 and 2010 and that served as the basis of the study. From the Climate Forecast System Reanalysis (CFSR) data it was possible to obtain the mean synoptic fields for the two sets of systems. These showed a more evident difference in the levels of 250 hPa and 500 hPa, indicating a strong contribution of the Jet Streak and of a trough in 500 hPa in the organization of the MCSs, absent condition in cases of unorganized convection. Using statistical methods, we obtained the best meteorological parameters that composed 4 new versions of MCS indexes. These were statistically evaluated from their ability to detect MCSs. The result was an MCS index for South America (SA-MCS Index) that was able to detect twice as many MCSs as the MCS Index in one of the distances parameters evaluated between the maximum index values points and the initiation position point of the MCSs observed. Although it was elaborated from MCSs lasting more than 6 hours, the SA-MCS Index was able to successfully detect the development and displacement in a evaluated case of MCS that had a shorter duration. In addition, it was successful with the use of forecast products from the Global Forecast System (GFS) model. In another study, throughout the warm season in Rio Grande do Sul (RS), the SA-MCS Index was evaluated, with a forecast horizon of 24 hours, daily. The results showed that all the MCSs occurring in RS, as well as all the severe weather events reported by the Civil Defense of RS, occurred on days with an indicative development of MCSs on RS according to the SA-MCS Index. Although the MCS Index was also able to detect all MCSs and severe events, it had a false alarm rate more than twice as high compared with developed SA-MCS Index. Another observed SA-MCS Index application was for the prediction of regions with potential for intense winds through coupling to wind gust indexes (Windex and Gustex), modified for the region, with a probability of detection higher than 80% of the cases with intense winds associated with MCSs, generating a false alarm rate that does not exceed 40%. Thus, there is a potential use of the SA-MCS Index coupled with predictive intense wind indexes that can be of great value to the energy and transport sectors. In addition, the SA-MCS Index used as a decision-making tool for the activation of high resolution simulations allows a considerable reduction of computational costs.